The comparison of novel serious games in ADHD screening and early diagnosis - Ściseł, Alicja; Szymańska, Kinga; Szyprowski, Karol; Trześniowska, Agata; Soroka, Ewelina (Current Problems of Psychiatry, 2024)
Introduction: Despite the increasing global prevalence of ADHD in children, research predominantly focuses on treatment rather than on screening. There is a pressing need for practical tools to identify this disorder. The objective of this review was to conduct a detailed analysis of the novel games used for ADHD screening and early diagnosis. Material and methods: Our interest was focused on comparing various aspects, such as effectiveness, types of parameters tested, characteristics of the research group, time consumption, and the kind of equipment necessary to conduct the game. Sources were gathered by exploring terms related to ADHD screening and diagnosis in gaming contexts via several databases. Inclusion criteria focused on papers from 2020 to 2024 in English and openly accessible. Ten clinical studies meeting the criteria were identified, analyzed, and compared in subsequent sections. Results: Our analysis has revealed that the games under discussion are characterized by distinct mechanics and measure different parameters related to ADHD. The methods of their validation are not standardized. These aspects make it challenging to compare them. Certain games incorporate advanced technologies to enhance the objectivity of the screening process. Conclusions: The results of our review confirm that the screening effectiveness comparable to that acquired by standardized tests could be obtained using serious games. Individuals with ADHD are at higher risk of addiction, though tailored video games can aid in the treatment of ADHD. However, there is a need to standardize the methodology for assessing the effectiveness of the games under analysis.